PERAN TEKNOLOGI DALAM PENENTUAN KEBIJAKAN PENGELOLAAN SUMBERDAYA AIR NASIONAL - Herlambang, Arie (Center for Environmental Technology, 2009)
In the national water resource management, the data is the basis for the calculation of water reserves. In a large scale and wide, searching the data will require substantial funding, as well as with the updates. Data colecting becomes a problem and not useful if not managed with the system efficiently and effectively. Technology occupies an important role in accelerating the work, such as remote sensing technology using a satellite to determine the condition of forests and water, or a weather that can see the concentration of clouds and wind movement. Determination of catchment areas of water and protected areas, may of them using remote sensing technology. Water treatment technologies for drinking water and the development of efficient recycling technology of waste water, is very supportive in increasing water use efficiency. Technological developments also influence government policy and the implementation of water resource management. National Policy of Water Resource Management is influenced by economic factors, environmental sustainability and socio-cultural conditions. The role of technology areÃ‚Â facilitate, accelerate and improve the efficiency of the process, so that the process can be more economical and environmental impact is reduced, and does not conflict with the socio-cultural conditions.Ã‚Â Keywords : Kebijakan nasional sumber daya air, potensi sda, teknologi pengolahan air